The diagrams of architecture - Garcia, Mark. (Chichester : Wiley, 2010)
"Diagrams of Architecture is the first anthology to represent - through texts and diagrams - the histories, theories and futures of architecture through the diagram." "Spanning the Pre-historic to the Parametric, Diagrams of Architecture illustrates over 250 diagrams and brings together 26 previously published and newly commissioned essays from leading international academics, architects, theorists and professional experts. These combine to define the past and future of the diagram's discourse. Prefaced with a critical introduction by Mark Garcia, each text investigates a central concept or dimension of the diagram ranging from socio-cultural studies, science, philosophy, technology, CAD/CAM, computing and cyberspace and virtual/digital design to methodology, environment/sustainability and phenomenological, poetic and art architecture; as well as interior, urban, engineering, interactive and landscape design."--BOOK JACKET.
Introduction : diagrams -- Introduction : Histories and theories of the diagrams of architecture / Mark Garcia -- Part I : Histories and theories of the diagrams of architecture. Part I : Diagrams -- Diagrams of diagrams : architectural abstraction and modern representation / Anthony Vidler -- Scientific management and the birth of the functional diagram / Hyungmin Pai -- Urban diagrams and urban modelling / David Grahame Shane -- Dummy text, or the diagrammatic basis of contemporary architecture / Robert E Somol -- Diagram : an original scene of writing / Peter Eisenman -- Poetics of the ideogram / Leon van Schaik -- Diagrams in multisensory and phenomenological architecture / Joy Monice Malnar and Frank Vodvarka -- The hammer and the song / Sandford Kwinter -- Part II : multidisciplinary dimensions of the diagrams of architecture. Part II : Diagrams -- Diagramming the interior / Mark Taylor -- Diagrams in landscape architecture / Jacky Bowring and Simon Swaffield -- Inhabiting the forest of symbols : from diagramming the city to the city as diagram / Brian McGrath -- Diagrams and their future in urban design / Peter A Hall -- Diagrams in structural engineering : applied diagrams, engineering precision / Hanif Kara -- Spatial notation and the magical operations of collage in the post-digital age / Neil Spiller -- Part III : Architects of the diagrams of architecture. Part III : Diagrams -- The diagrams of Bernard Tschumi / Bernard Tschumi (Bernard Tschumi Architects) interviewed by Mark Garcia -- The diagrams and the becoming unmotivated of the sign / Peter Eisenman (Eisenman Architects) -- Expressive abstractions : the diagrams of Will Alsop / Will Alsop interviewed by Mark Garcia -- Diagrams / Ben van Berkel and Caroline Bos (UNStudio) -- Diagramming the contemporary : OMA's little helper in the quest for the new / Wouter Deen and Udo Garritzmann (OMA) -- Between ideas and matters : icons, indexes, diagrams, drawings and graphs / Alejandro Zaera-Polo (Foreign Office Architects) -- Metacity/Datatown / Winy Maas (MVRDV) -- Atlas of novel tectonics / Jesse Reiser and Nanako Umemoto (Reiser + Umemoto) -- Parametric diagrams / Patrik Schumacher (Zaha Hadid Architects) -- NOX diagrams / Lars Spuybroek (NOX) -- Part IV : Epilogues. Part IV : Diagrams -- Architectural evolution : the pulsations of time / Charles Jencks -- Epilogue (A beginning of other diagrams of architecture and the futures of the diagrams of architecture) / Mark Garcia -- Select bibliography -- Index.
Includes bibliographical references (p. 317) and index.
ARC
Keywords: Architectural drawing; Architecture -- Charts, diagrams, etc